2016
DOI: 10.1002/anie.201610072
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Reactivity of Electron‐Precise B−B Single and Multiple Bonds

Abstract: Recent years have seen rapid advances in the chemistry of small molecules containing electron-precise boron-boron bonds. This Review provides an overview of the latest methods for the controlled synthesis of B-B single and multiple bonds as well as the ever-expanding range of reactivity displayed by B-B multiple bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
167
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 181 publications
(381 reference statements)
6
167
0
14
Order By: Relevance
“…[10] Eine Mehrfachbindung konnte erstmalig synthetisch durch Ein-und Zweielektronenreduktion von Diboranen [11][12][13][14] oder Dialanen [15][16][17][18] realisiert werden. [10] Eine Mehrfachbindung konnte erstmalig synthetisch durch Ein-und Zweielektronenreduktion von Diboranen [11][12][13][14] oder Dialanen [15][16][17][18] realisiert werden.…”
unclassified
“…[10] Eine Mehrfachbindung konnte erstmalig synthetisch durch Ein-und Zweielektronenreduktion von Diboranen [11][12][13][14] oder Dialanen [15][16][17][18] realisiert werden. [10] Eine Mehrfachbindung konnte erstmalig synthetisch durch Ein-und Zweielektronenreduktion von Diboranen [11][12][13][14] oder Dialanen [15][16][17][18] realisiert werden.…”
unclassified
“…Daraufhin kommt es zur Bildung eines sechsgliedri-gen Übergangzustands,w oraufhin sowohl der protische als auch der hydridische Wasserstoff in einem konzertierten Mechanismus an die ungesättigte Bindung abgegeben werden (Abbildung 1a). [13] Wirh aben dabei gezeigt, dass mit N-heterocyclischen Carbenen (NHCs) stabilisierte Diheteroaryldiborene eine spontane syn-Hydroborierung mit Catecholboran [14] und 9-Borabicyclo[3.3.1]nonan (9-BBN) [15] eingehen. Anschließend findet ein Protonentransfer zum borylierten Kohlenstoffatom statt, woraufhin das Aminoboran als Nebenprodukt freigesetzt wird (Abbildung 1b).…”
unclassified
“…X-ray crystallography unequivocally established the constitution of the product, however,the data quality was too poor for ar eliable determination of geometric parameters (see the Supporting Information). [11] In principle,the [(Me 3 Si) 3 C] À anion could also act as ar educing agent rather than aB rønsted base toward 1H 2 and thereby trigger an electron-transfer/H-abstraction scenario.T he following observations argue against such aradical mechanism:1)Aputative [(Me 3 Si) 3 C]C intermediate should preferentially react with the abundant solvent molecules and would then no longer be available to abstract an H atom from [1H 2 ]C À ;m oreover,w en ever observed the formation of (Me 3 Si) 3 CD when the reaction was carried out in [D 8 ]THF.2)W ehave previously shown that [1H 2 ]C À tends to undergo fast structural rearrangement reactions,which is not in accord with the highly selective conversion reported here. In all of the independent molecules,the [Li(Et 2 O) 2 ] + cations are located side-on to the electron-rich B À Bbonds and close to the positions previously occupied by the m-H atoms.All key bond lengths and angles of [1H] À are very similar to those of the corresponding K + salt;the same is true for the NMR data (see the Supporting Information for full details).…”
mentioning
confidence: 99%
“…We therefore repeated the reaction in Et 2 Otoobtain crystals of [Li(Et 2 O) 2 ][1H],which allowed asatisfactory structure analysis.The asymmetric unit contains two whole and two half independent molecules, which differ mainly in the twist of their anionic moieties ( Figure 2; the torsion angles between the central CÀCb onds of the respective 2,2'-biphenylylene bridges range between 4.2(2)8 8 and 32.1(3) 8 8). [11] 3) Thep resence of nBu 3 SnH, ap rominent spintrapping reagent, [26] did not change the reaction outcome;the compound rather remained untouched, according to NMR spectroscopy.4 )The use of (Me 3 Si) 2 NM (M = Li, K) instead of (Me 3 Si) 3 CLi also resulted in the quantitative formation of M[1H],e ven though the amide is aw eaker reducing agent than the methanide. [11] In principle,the [(Me 3 Si) 3 C] À anion could also act as ar educing agent rather than aB rønsted base toward 1H 2 and thereby trigger an electron-transfer/H-abstraction scenario.T he following observations argue against such aradical mechanism:1)Aputative [(Me 3 Si) 3 C]C intermediate should preferentially react with the abundant solvent molecules and would then no longer be available to abstract an H atom from [1H 2 ]C À ;m oreover,w en ever observed the formation of (Me 3 Si) 3 CD when the reaction was carried out in [D 8 ]THF.2)W ehave previously shown that [1H 2 ]C À tends to undergo fast structural rearrangement reactions,which is not in accord with the highly selective conversion reported here.…”
mentioning
confidence: 99%
See 1 more Smart Citation